Business cycle convergence or decoupling? Economic adjustment in CESEE during the crisis - Simon Gächter; Alesandra Riedl; Doris Ritzberger-Grünwald (Bank of Finland, Institute for Economies in Transition (BOFIT), 2013)
We analyze business cycle convergence in the EU by focusing on the decoupling vs. convergence hypothesis for central, eastern and south eastern Europe (CESEE). In a nutshell, we find that business cycles in CESEE have decoupled considerably from the euro area (EA) during the financial crisis in terms of both cyclical dispersion (i.e. the deviation of output gaps) and cyclical correlation. The results are mainly driven by smaller countries, which can be explained by the fact that small economies seem to have larger cyclical swings as they are more dependent on external demand, which causes a decoupling in terms of higher output gap deviations from the EA cycle in times of economic crises. At the same time, this does not necessarily affect business cycle synchronization as measured by cyclical correlations, where the strength of the linear relationship of two cycles is measured. However, despite the recent declines in the co-movement, we generally observe high correlation levels of CESEE countries with the EA after their EU accession in 2004. Finally, we find a significant decoupling of trend growth rates between EA and CESEE until the onset of the financial crises. Since the beginning of the crisis, trend growth rates have declined both in CESEE and the EA with the trend growth differential decreasing significantly from about three to below two percentage points in 2011.
URN:NBN:fi:bof-201408071921
Keywords: E32; E52; F15; F33; F44; 330; Business cycles; EMU; CESEE; optimum currency areas